PROBLEMATIKA PRIVASI DALAM MEDIA (KAJIAN PRIVASI SEBAGAI NILAI MORAL) - Muhamad Taufik; Muzairi Muzairi; Afriadi Putra (Refleksi: Jurnal Filsafat dan Pemikiran Keislaman, 2016)
Discussion and research on media as a discourse could not be separated from the connection between the language that used in it, the knowledge that underlying, as well as other forms of interests and power that operating behind the language. That means, the conversation about media inevitably cannot be separated from the ideology that formed it, which is finally affects the language (style, expression, vocabulary, signs) that used and the knowledge (justice, truth, reality) that generated it. We are aware the discussion of media and communication order cannot be separated from the interests behind the media, especially the interests of the information that conveyed. Eviction ofprivacy in communication practices indeed became serious problem because it involves self-esteem, which ultimately creates many prolonged polemic. Privacy as a right or a right to control unwanted publicity, become someone's personal affairs personal because our problem has occurred mistakenly believe that a public figureby itself does not have privacy inthe public. For this reason, this research is conducted, namely the attempt to try to analyse the privacy and moral value in media that eligible to be criticized.